Nationality Diversity in Academia: What is the Problem Represented to be? - Maximova-Mentzoni, Tatiana; Egeland, Cathrine (Nordic Journal of Working Life Studies, 2019)
This article investigates problem representations of nationality diversity at higher education and research institutions in Norway and in the other Nordic countries. Nationality diversity refers to different nationalities among academic staff that increases language, value and information diversity in organizations. Employing a ‘What’s the problem represented to be’ approach, we uncover problem representations identified in previous Nordic research on nationality diversity in academia as well as in a recent case study on nationality diversity at Norwegian higher education and research institutions. While the literature review identifies different problem representations, explores their underlying conceptual logics and describes how these problem representations are formed, the Norwegian case study intends to address problem representations that seem to be left unproblematic both in previous research and organizational practices in Norwegian academia.